High-strength crossed composite film and preparation method thereof
By cross-combining high-density polyethylene, linear low-density polyethylene and other materials and coating polyurethane coatings on the surface, the limitations of traditional film materials in terms of strength and waterproofness are solved, and a cross-combining film with high strength and excellent waterproof performance is achieved.
Patent Information
- Application Number
- CN202510138885.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-29
AI Technical Summary
Traditional film materials have limitations in strength, waterproofness, corrosion resistance, thermal stability, etc., and it is difficult to show superior performance in a strict application environment.
Materials such as high-density polyethylene, linear low-density polyethylene, isocyanate modified polyethylene, maleic anhydride grafted polyethylene, mesoporous silica and hydrophobic carboxymethyl cellulose are cross-composite, and high-strength cross-composite film is formed through extrusion, blow molding, stretching and rotary cutting, and polyurethane coating is applied to the surface to improve hydrophobicity.
The film has significantly improved the tensile strength, tear resistance and waterproof properties, allowing it to show superior performance in more complex application environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thin films, in particular to a high-strength cross-composite thin film and a preparation method thereof. Background Art
[0002] High-strength cross-laminated films are widely used in the field of building waterproofing as the face and base membranes of building waterproofing. Traditional film materials, such as polyethylene and polypropylene, usually have certain limitations in strength, waterproofness, corrosion resistance, thermal stability, etc., which restrict their application in more stringent scenarios. Cross-laminated films, through alternating composite structures in different directions, further enhance the tensile strength and tear resistance of the membrane material, making it perform better in more complex application environments.
[0003] In order to solve the above problems and improve the strength and water resistance of the film, the present invention provides a high-strength cross-composite film and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide a high-strength cross-composite film and a preparation method thereof, so as to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a high-strength cross-composite film comprises the following steps: Step 1: uniformly mix linear low-density polyethylene, maleic anhydride grafted polyethylene and mesoporous silica, extrude, pelletize and dry to obtain a masterbatch; Step 2: taking high-density polyethylene, linear low-density polyethylene, isocyanate-modified polyethylene, maleic anhydride-grafted polyethylene, masterbatch, paraffin, antioxidant, stabilizer, extruding, blow molding, stretching at 100° C., rotary cutting to obtain a film, cross-compounding to obtain a composite film, drying, and rolling to obtain a cross-compounded film; Step 3: Take polyurethane and acetone, stir evenly, add hydrophobic carboxymethyl cellulose, and disperse by ultrasonic to obtain polyurethane coating; Step 4: Take the cross-composite film, apply the polyurethane coating on the surface of the cross-composite film, and dry it to obtain a high-strength cross-composite film.
[0006] More optimally, the preparation method of the hydrophobic carboxymethyl cellulose is: take paraffin-coated carboxymethyl cellulose and acetone, stir evenly, add dodecyl mercaptan and benzoin dimethyl ether, irradiate with ultraviolet light for 2-2.5 hours in an ice-water bath, centrifuge, add cyclohexane, stir evenly, centrifuge, wash, add isopropanol, add β-mercaptoethylamine and benzoin dimethyl ether, stir evenly, irradiate with ultraviolet light for 2-2.5 hours, centrifuge, add amino silicone oil and ethyl acetate, stir for 4-5 hours, centrifuge, and dry to obtain hydrophobic carboxymethyl cellulose.
[0007] More optimally, the cross-composite film includes the following components, by weight: 85-90 parts of high-density polyethylene, 40-45 parts of linear low-density polyethylene, 20-22 parts of isocyanate-modified polyethylene, 15-16 parts of maleic anhydride-grafted polyethylene, 3-3.5 parts of masterbatch, 6-8 parts of paraffin, 0.8-1 parts of antioxidant, and 0.5-0.6 parts of stabilizer.
[0008] More optimally, the preparation method of the isocyanate-modified polyethylene is: take high-density polyethylene, styrene, diisopropyl peroxide, and 3-isopropyl-dimethylbenzyl isocyanate, mix them evenly, heat them to 185-190° C., react for 10-12 minutes, filter, and dry to obtain isocyanate-modified polyethylene.
[0009] More optimally, the preparation method of the mesoporous silica is: take deionized water and ethanol, stir evenly, add hexadecyltrimethylammonium bromide, add ammonia water to adjust the pH value to 12, ultrasonically disperse for 20-30 minutes, add tetraethyl silicate, stir for 12-14 hours, centrifuge, wash, dry, and calcine to obtain mesoporous silica.
[0010] Preferably, the preparation method of the paraffin-coated carboxymethyl cellulose comprises the following steps: Step 1: Take carboxymethyl cellulose and hydrochloric acid solution, stir for 10-20 minutes, filter, wash, dry, add a mixed solution of KH570, ethanol and deionized water, ultrasonically disperse, add glacial acetic acid to adjust the pH to 4-4.5, react at 80-85°C for 5-6 hours, wash and dry to obtain modified carboxymethyl cellulose; Step 2: Take hexadecyltrimethylammonium bromide, modified carboxymethyl cellulose and deionized water, ultrasonically disperse for 30-40 minutes, add paraffin, heat to 75-80°C, emulsify for 50-70 minutes, cool, centrifuge and wash to obtain carboxymethyl cellulose coated with paraffin.
[0011] More optimally, the stabilizer is any one or more of tri(2-ethylhexyl)tin sulfosuccinate and tin stearate.
[0012] More optimally, the antioxidant is any one or more of butyl hydroxybenzoate and triphenyl phosphite.
[0013] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention prepares a hydrophobic carboxymethyl cellulose, which is widely used in the barrier field, has good film-forming density and adhesion, and can form a stable fiber structure. The present invention uses dodecyl mercaptan for modification to enhance its hydrophobicity, and then adds amino silicone oil for further hydrophobic modification.
[0014] 2. The present invention uses isocyanate to modify polyethylene. The combination of isocyanate and polyethylene usually strengthens the cross-linking effect between polyethylene molecular chains, thereby improving the mechanical strength and toughness of polyethylene and increasing the strength of the composite film.
[0015] 3. The amino silicone oil of the present invention can improve the hydrophobicity. At the same time, the amino group can produce a chemical cross-linking reaction with the isocyanate in the polyethylene to firmly combine the coating and the composite film matrix, thereby improving the hydrophobicity of the composite film. DETAILED DESCRIPTION
[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] The sources and types of the substances involved in the present invention are not particularly limited, and exemplary examples include: Maleic anhydride grafted polyethylene: Model: ZJ-800E, which can be purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.; Linear low-density polyethylene: Model: L909897, which can be purchased from Maclean; High-density polyethylene: Model: H790495, which can be purchased from Maclean.
[0018] Embodiment 1: A method for preparing a high-strength cross-composite film, comprising the following steps: Step 1: Preparation of hydrophobic carboxymethyl cellulose: Take 0.5g carboxymethyl cellulose and 100mL 5mol / L hydrochloric acid solution, stir for 15min, filter, wash and dry, add 2g KH570 and 50mL ethanol and deionized water mixed solution with a volume ratio of 2:3, ultrasonically disperse, add glacial acetic acid to adjust the pH to 4.2, react at 82℃ for 5.5h, wash and dry to obtain modified carboxymethyl cellulose; Take 0.2 g of hexadecyltrimethylammonium bromide, 0.5 g of modified carboxymethyl cellulose, and 30 mL of deionized water, and ultrasonically disperse for 35 min, add 2 g of paraffin, heat to 78 ° C, emulsify for 60 min, cool, centrifuge, and wash to obtain carboxymethyl cellulose coated with paraffin; Take 0.4g paraffin-coated carboxymethyl cellulose and 30mL acetone, stir evenly, add 0.06g dodecyl mercaptan and 0.015g benzoin dimethyl ether, irradiate with UV light for 2.2h in an ice-water bath, centrifuge, add 40mL cyclohexane, stir evenly, centrifuge, wash, add 30mL isopropanol, add 0.05g β-mercaptoethylamine and 0.012g benzoin dimethyl ether, stir evenly, irradiate with UV light for 2.2h, centrifuge, add 3g amino silicone oil and 50mL ethyl acetate, stir for 4.5h, centrifuge and dry to obtain hydrophobic carboxymethyl cellulose; Step 2: Preparation of mesoporous silica: Take 100 mL of deionized water and 120 g of ethanol, stir evenly, add 4 g of hexadecyltrimethylammonium bromide, add ammonia water to adjust the pH value to 12, ultrasonically disperse for 25 min, add 5.5 g of tetraethyl silicate, stir for 13 h, centrifuge, wash, dry, and calcine to obtain mesoporous silica; Step 3: Preparation of isocyanate modified polyethylene: Take 50g high-density polyethylene, 1.2mL styrene, 0.32g diisopropyl peroxide, and 3mL 3-isopropyl-dimethylbenzyl isocyanate, mix them evenly, heat to 188°C, react for 11min, filter, and dry to obtain isocyanate-modified polyethylene; Step 4: Preparation of polyurethane coating: Take 5 g of polyurethane and 25 mL of acetone, stir evenly, add 0.5 g of hydrophobic carboxymethyl cellulose, and disperse by ultrasonic to obtain a polyurethane coating; Step 5: Preparation of high-strength cross-laminated film: 50g of linear low-density polyethylene, 38g of maleic anhydride grafted polyethylene, and 10g of mesoporous silica were mixed uniformly, extruded, pelletized, and dried to obtain a masterbatch; High-density polyethylene, linear low-density polyethylene, isocyanate-modified polyethylene, maleic anhydride-grafted polyethylene, masterbatch, paraffin, antioxidant, stabilizer are extruded, blow-molded, stretched at 100°C, and rotary cut to obtain a film, six films are cross-laminated at an angle of 85° to obtain a composite film, and the film is dried and rolled to obtain a cross-laminated film; The cross-composite film comprises the following components, by weight: 88 parts of high-density polyethylene, 42 parts of linear low-density polyethylene, 21 parts of isocyanate-modified polyethylene, 15.5 parts of maleic anhydride-grafted polyethylene, 3 parts of masterbatch, 7 parts of paraffin wax, 0.9 parts of antioxidant butyl hydroxybenzoate, and 0.55 parts of stabilizer tri(2-ethylhexyl)tin sulfosuccinate; Take the cross-laminated film, apply the polyurethane coating on the surface of the cross-laminated film, dry it, and the coating thickness is 5µm to obtain a high-strength cross-laminated film.
[0019] Embodiment 2: A method for preparing a high-strength cross-composite film, comprising the following steps: Step 1: Preparation of hydrophobic carboxymethyl cellulose: Take 0.5g carboxymethyl cellulose and 100mL 5mol / L hydrochloric acid solution, stir for 10min, filter, wash and dry, add 2g KH570 and 50mL ethanol and deionized water mixed solution with a volume ratio of 2:3, ultrasonically disperse, add glacial acetic acid to adjust the pH to 4, react at 80℃ for 5-6h, wash and dry to obtain modified carboxymethyl cellulose; Take 0.2 g of hexadecyltrimethylammonium bromide, 0.5 g of modified carboxymethyl cellulose, and 30 mL of deionized water, and ultrasonically disperse for 30 min. Add 2 g of paraffin wax, heat to 75 ° C, emulsify for 50 min, cool, centrifuge, and wash to obtain carboxymethyl cellulose coated with paraffin wax. Take 0.4g paraffin-coated carboxymethyl cellulose and 30mL acetone, stir evenly, add 0.06g dodecyl mercaptan and 0.015g benzoin dimethyl ether, irradiate with UV light for 2h in an ice-water bath, centrifuge, add 40mL cyclohexane, stir evenly, centrifuge, wash, add 30mL isopropanol, add 0.05g β-mercaptoethylamine and 0.012g benzoin dimethyl ether, stir evenly, irradiate with UV light for 2h, centrifuge, add 3g amino silicone oil and 50mL ethyl acetate, stir for 4h, centrifuge and dry to obtain hydrophobic carboxymethyl cellulose; Step 2: Preparation of mesoporous silica: Take 100 mL of deionized water and 120 g of ethanol, stir evenly, add 4 g of hexadecyltrimethylammonium bromide, add ammonia water to adjust the pH value to 12, ultrasonically disperse for 20 min, add 5.5 g of tetraethyl silicate, stir for 12 h, centrifuge, wash, dry, and calcine to obtain mesoporous silica; Step 3: Preparation of isocyanate modified polyethylene: Take 50g high-density polyethylene, 1.2mL styrene, 0.32g diisopropyl peroxide, and 3mL 3-isopropyl-dimethylbenzyl isocyanate, mix them evenly, heat to 185°C, react for 10min, filter, and dry to obtain isocyanate-modified polyethylene; Step 4: Preparation of polyurethane coating: Take 5 g of polyurethane and 25 mL of acetone, stir evenly, add 0.5 g of hydrophobic carboxymethyl cellulose, and disperse by ultrasonic to obtain a polyurethane coating; Step 5: Preparation of high-strength cross-laminated film: 50g of linear low-density polyethylene, 38g of maleic anhydride grafted polyethylene, and 10g of mesoporous silica were mixed uniformly, extruded, pelletized, and dried to obtain a masterbatch; High-density polyethylene, linear low-density polyethylene, isocyanate-modified polyethylene, maleic anhydride-grafted polyethylene, masterbatch, paraffin, antioxidant, stabilizer are extruded, blow-molded, stretched at 100°C, and rotary cut to obtain a film, six films are cross-laminated at an angle of 85° to obtain a composite film, and the film is dried and rolled to obtain a cross-laminated film; The cross-composite film comprises the following components, by weight: 85 parts of high-density polyethylene, 40 parts of linear low-density polyethylene, 20 parts of isocyanate-modified polyethylene, 15 parts of maleic anhydride-grafted polyethylene, 3 parts of masterbatch, 6 parts of paraffin wax, 0.8 parts of antioxidant triphenyl phosphite, and 0.5 parts of stabilizer tin stearate; Take the cross-laminated film, apply the polyurethane coating on the surface of the cross-laminated film, dry it, and the coating thickness is 5µm to obtain a high-strength cross-laminated film.
[0020] Embodiment 3: A method for preparing a high-strength cross-composite film, comprising the following steps: Step 1: Preparation of hydrophobic carboxymethyl cellulose: Take 0.5g carboxymethyl cellulose and 100mL 5mol / L hydrochloric acid solution, stir for 20min, filter, wash and dry, add 2g KH570 and 50mL ethanol and deionized water mixed solution with a volume ratio of 2:3, ultrasonically disperse, add glacial acetic acid to adjust the pH to 4.5, react at 85℃ for 6h, wash and dry to obtain modified carboxymethyl cellulose; Take 0.2 g of hexadecyltrimethylammonium bromide, 0.5 g of modified carboxymethyl cellulose, and 30 mL of deionized water, and ultrasonically disperse for 40 min, add 2 g of paraffin, heat to 80 ° C, emulsify for 70 min, cool, centrifuge, and wash to obtain carboxymethyl cellulose coated with paraffin; Take 0.4g paraffin-coated carboxymethyl cellulose and 30mL acetone, stir evenly, add 0.06g dodecyl mercaptan and 0.015g benzoin dimethyl ether, irradiate with UV light for 2.5h in an ice-water bath, centrifuge, add 40mL cyclohexane, stir evenly, centrifuge, wash, add 30mL isopropanol, add 0.05g β-mercaptoethylamine and 0.012g benzoin dimethyl ether, stir evenly, irradiate with UV light for 2.5h, centrifuge, add 3g amino silicone oil and 50mL ethyl acetate, stir for 5h, centrifuge and dry to obtain hydrophobic carboxymethyl cellulose; Step 2: Preparation of mesoporous silica: Take 100 mL of deionized water and 120 g of ethanol, stir evenly, add 4 g of hexadecyltrimethylammonium bromide, add ammonia water to adjust the pH value to 12, ultrasonically disperse for 30 min, add 5.5 g of tetraethyl silicate, stir for 14 h, centrifuge, wash, dry, and calcine to obtain mesoporous silica; Step 3: Preparation of isocyanate modified polyethylene: Take 50g high-density polyethylene, 1.2mL styrene, 0.32g diisopropyl peroxide, and 3mL 3-isopropyl-dimethylbenzyl isocyanate, mix them evenly, heat to 190°C, react for 12min, filter, and dry to obtain isocyanate-modified polyethylene; Step 4: Preparation of polyurethane coating: Take 5 g of polyurethane and 25 mL of acetone, stir evenly, add 0.5 g of hydrophobic carboxymethyl cellulose, and disperse by ultrasonic to obtain a polyurethane coating; Step 5: Preparation of high-strength cross-laminated film: 50g of linear low-density polyethylene, 38g of maleic anhydride grafted polyethylene, and 10g of mesoporous silica were mixed uniformly, extruded, pelletized, and dried to obtain a masterbatch; High-density polyethylene, linear low-density polyethylene, isocyanate-modified polyethylene, maleic anhydride-grafted polyethylene, masterbatch, paraffin, antioxidant, stabilizer are extruded, blow-molded, stretched at 100°C, and rotary cut to obtain a film, six films are cross-laminated at an angle of 85° to obtain a composite film, and the film is dried and rolled to obtain a cross-laminated film; The cross-composite film comprises the following components, by weight: 90 parts of high-density polyethylene, 45 parts of linear low-density polyethylene, 22 parts of isocyanate-modified polyethylene, 16 parts of maleic anhydride-grafted polyethylene, 3.5 parts of masterbatch, 8 parts of paraffin wax, 1 part of antioxidant butyl hydroxybenzoate, and 0.6 parts of stabilizer tin stearate; Take the cross-laminated film, apply the polyurethane coating on the surface of the cross-laminated film, dry it, and the coating thickness is 5µm to obtain a high-strength cross-laminated film.
[0021] Comparative Example 1: No amino silicone oil was added, and the rest was the same as Example 1: Step 1: Preparation of hydrophobic carboxymethyl cellulose: Take 0.5g carboxymethyl cellulose and 100mL 5mol / L hydrochloric acid solution, stir for 15min, filter, wash and dry, add 2g KH570 and 50mL ethanol and deionized water mixed solution with a volume ratio of 2:3, ultrasonically disperse, add glacial acetic acid to adjust the pH to 4.2, react at 82℃ for 5.5h, wash and dry to obtain modified carboxymethyl cellulose; Take 0.2 g of hexadecyltrimethylammonium bromide, 0.5 g of modified carboxymethyl cellulose, and 30 mL of deionized water, and ultrasonically disperse for 35 min, add 2 g of paraffin, heat to 78 ° C, emulsify for 60 min, cool, centrifuge, and wash to obtain carboxymethyl cellulose coated with paraffin; Take 0.4 g paraffin-coated carboxymethyl cellulose and 30 mL acetone, stir evenly, add 0.06 g dodecyl mercaptan and 0.015 g benzoin dimethyl ether, irradiate with UV light for 2.2 h in an ice-water bath, centrifuge, add 40 mL cyclohexane, stir evenly, centrifuge, wash, add 30 mL isopropanol, add 0.05 g β-mercaptoethylamine and 0.012 g benzoin dimethyl ether, stir evenly, irradiate with UV light for 2.2 h, centrifuge, and dry to obtain hydrophobic carboxymethyl cellulose; Step 2: Preparation of mesoporous silica: Take 100 mL of deionized water and 120 g of ethanol, stir evenly, add 4 g of hexadecyltrimethylammonium bromide, add ammonia water to adjust the pH value to 12, ultrasonically disperse for 25 min, add 5.5 g of tetraethyl silicate, stir for 13 h, centrifuge, wash, dry, and calcine to obtain mesoporous silica; Step 3: Preparation of isocyanate modified polyethylene: Take 50g high-density polyethylene, 1.2mL styrene, 0.32g diisopropyl peroxide, and 3mL 3-isopropyl-dimethylbenzyl isocyanate, mix them evenly, heat to 188°C, react for 11min, filter, and dry to obtain isocyanate-modified polyethylene; Step 4: Preparation of polyurethane coating: Take 5 g of polyurethane and 25 mL of acetone, stir evenly, add 0.5 g of hydrophobic carboxymethyl cellulose, and disperse by ultrasonic to obtain a polyurethane coating; Step 5: Preparation of high-strength cross-laminated film: 50g of linear low-density polyethylene, 38g of maleic anhydride grafted polyethylene, and 10g of mesoporous silica were mixed uniformly, extruded, pelletized, and dried to obtain a masterbatch; High-density polyethylene, linear low-density polyethylene, isocyanate-modified polyethylene, maleic anhydride-grafted polyethylene, masterbatch, paraffin, antioxidant, stabilizer are extruded, blow-molded, stretched at 100°C, and rotary cut to obtain a film, six films are cross-laminated at an angle of 85° to obtain a composite film, and the film is dried and rolled to obtain a cross-laminated film; The cross-composite film comprises the following components, by weight: 88 parts of high-density polyethylene, 42 parts of linear low-density polyethylene, 21 parts of isocyanate-modified polyethylene, 15.5 parts of maleic anhydride-grafted polyethylene, 3 parts of masterbatch, 7 parts of paraffin wax, 0.9 parts of antioxidant butyl hydroxybenzoate, and 0.55 parts of stabilizer tri(2-ethylhexyl)tin sulfosuccinate; Take the cross-laminated film, apply the polyurethane coating on the surface of the cross-laminated film, dry it, and the coating thickness is 5µm to obtain a high-strength cross-laminated film.
[0022] Comparative Example 2: The polyethylene is not modified by using isocyanate, and the rest is the same as Example 1: Step 1: Preparation of hydrophobic carboxymethyl cellulose: Take 0.5g carboxymethyl cellulose and 100mL 5mol / L hydrochloric acid solution, stir for 15min, filter, wash and dry, add 2g KH570 and 50mL ethanol and deionized water mixed solution with a volume ratio of 2:3, ultrasonically disperse, add glacial acetic acid to adjust the pH to 4.2, react at 82℃ for 5.5h, wash and dry to obtain modified carboxymethyl cellulose; Take 0.2 g of hexadecyltrimethylammonium bromide, 0.5 g of modified carboxymethyl cellulose, and 30 mL of deionized water, and ultrasonically disperse for 35 min, add 2 g of paraffin, heat to 78 ° C, emulsify for 60 min, cool, centrifuge, and wash to obtain carboxymethyl cellulose coated with paraffin; Take 0.4g paraffin-coated carboxymethyl cellulose and 30mL acetone, stir evenly, add 0.06g dodecyl mercaptan and 0.015g benzoin dimethyl ether, irradiate with UV light for 2.2h in an ice-water bath, centrifuge, add 40mL cyclohexane, stir evenly, centrifuge, wash, add 30mL isopropanol, add 0.05g β-mercaptoethylamine and 0.012g benzoin dimethyl ether, stir evenly, irradiate with UV light for 2.2h, centrifuge, add 3g amino silicone oil and 50mL ethyl acetate, stir for 4.5h, centrifuge and dry to obtain hydrophobic carboxymethyl cellulose; Step 2: Preparation of mesoporous silica: Take 100 mL of deionized water and 120 g of ethanol, stir evenly, add 4 g of hexadecyltrimethylammonium bromide, add ammonia water to adjust the pH value to 12, ultrasonically disperse for 25 min, add 5.5 g of tetraethyl silicate, stir for 13 h, centrifuge, wash, dry, and calcine to obtain mesoporous silica; Step 3: Preparation of polyurethane coating: Take 5 g of polyurethane and 25 mL of acetone, stir evenly, add 0.5 g of hydrophobic carboxymethyl cellulose, and disperse by ultrasonic to obtain a polyurethane coating; Step 4: Preparation of high-strength cross-laminated film: 50g of linear low-density polyethylene, 38g of maleic anhydride grafted polyethylene, and 10g of mesoporous silica were mixed uniformly, extruded, pelletized, and dried to obtain a masterbatch; High-density polyethylene, linear low-density polyethylene, maleic anhydride grafted polyethylene, masterbatch, paraffin, antioxidant, stabilizer are extruded, blown, stretched at 100°C, and rotary cut to obtain a film, six films are cross-laminated at an angle of 85° to obtain a composite film, and the film is dried and rolled to obtain a cross-laminated film; The cross-composite film comprises the following components, by weight: 88 parts of high-density polyethylene, 42 parts of linear low-density polyethylene, 15.5 parts of maleic anhydride grafted polyethylene, 3 parts of masterbatch, 7 parts of paraffin wax, 0.9 parts of antioxidant butyl hydroxybenzoate, and 0.55 parts of stabilizer tri(2-ethylhexyl)tin sulfosuccinate; Take the cross-laminated film, apply the polyurethane coating on the surface of the cross-laminated film, dry it, and the coating thickness is 5µm to obtain a high-strength cross-laminated film.
[0023] Comparative Example 3: No dodecyl mercaptan was added, and the rest was the same as Example 1: Step 1: Preparation of hydrophobic carboxymethyl cellulose: Take 0.5g carboxymethyl cellulose and 100mL 5mol / L hydrochloric acid solution, stir for 15min, filter, wash and dry, add 2g KH570 and 50mL ethanol and deionized water mixed solution with a volume ratio of 2:3, ultrasonically disperse, add glacial acetic acid to adjust the pH to 4.2, react at 82℃ for 5.5h, wash and dry to obtain modified carboxymethyl cellulose; Take 0.2 g of hexadecyltrimethylammonium bromide, 0.5 g of modified carboxymethyl cellulose, and 30 mL of deionized water, and ultrasonically disperse for 35 min, add 2 g of paraffin, heat to 78 ° C, emulsify for 60 min, cool, centrifuge, and wash to obtain carboxymethyl cellulose coated with paraffin; Take 0.4g paraffin-coated carboxymethyl cellulose and 30mL acetone, stir evenly, add 0.015g benzoin dimethyl ether, irradiate with UV light for 2.2h in an ice-water bath, centrifuge, add 40mL cyclohexane, stir evenly, centrifuge, wash, add 30mL isopropanol, add 0.05g β-mercaptoethylamine, 0.012g benzoin dimethyl ether, stir evenly, irradiate with UV light for 2.2h, centrifuge, add 3g amino silicone oil and 50mL ethyl acetate, stir for 4.5h, centrifuge, and dry to obtain hydrophobic carboxymethyl cellulose; Step 2: Preparation of mesoporous silica: Take 100 mL of deionized water and 120 g of ethanol, stir evenly, add 4 g of hexadecyltrimethylammonium bromide, add ammonia water to adjust the pH value to 12, ultrasonically disperse for 25 min, add 5.5 g of tetraethyl silicate, stir for 13 h, centrifuge, wash, dry, and calcine to obtain mesoporous silica; Step 3: Preparation of isocyanate modified polyethylene: Take 50g high-density polyethylene, 1.2mL styrene, 0.32g diisopropyl peroxide, and 3mL 3-isopropyl-dimethylbenzyl isocyanate, mix them evenly, heat to 188°C, react for 11min, filter, and dry to obtain isocyanate-modified polyethylene; Step 4: Preparation of polyurethane coating: Take 5 g of polyurethane and 25 mL of acetone, stir evenly, add 0.5 g of hydrophobic carboxymethyl cellulose, and disperse by ultrasonic to obtain a polyurethane coating; Step 5: Preparation of high-strength cross-laminated film: 50g of linear low-density polyethylene, 38g of maleic anhydride grafted polyethylene, and 10g of mesoporous silica were mixed uniformly, extruded, pelletized, and dried to obtain a masterbatch; High-density polyethylene, linear low-density polyethylene, isocyanate-modified polyethylene, maleic anhydride-grafted polyethylene, masterbatch, paraffin, antioxidant, stabilizer are extruded, blow-molded, stretched at 100°C, and rotary cut to obtain a film, six films are cross-laminated at an angle of 85° to obtain a composite film, and the film is dried and rolled to obtain a cross-laminated film; The cross-composite film comprises the following components, by weight: 88 parts of high-density polyethylene, 42 parts of linear low-density polyethylene, 21 parts of isocyanate-modified polyethylene, 15.5 parts of maleic anhydride-grafted polyethylene, 3 parts of masterbatch, 7 parts of paraffin wax, 0.9 parts of antioxidant butyl hydroxybenzoate, and 0.55 parts of stabilizer tri(2-ethylhexyl)tin sulfosuccinate; Take the cross-laminated film, apply the polyurethane coating on the surface of the cross-laminated film, dry it, and the coating thickness is 5µm to obtain a high-strength cross-laminated film.
[0024] experiment: The high-strength cross-laminated films prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were cut into samples of 220 mm × 25 mm × 2 mm for performance testing, and their water contact angles were tested to characterize their waterproof properties; the water vapor transmission rate was tested using a gas barrier instrument, and the data obtained were as follows:
[0025] Conclusion: From the comparison of the data in the table, it can be seen that in Example 1, amino silicone oil is not added, and the hydrophobicity of the high-strength cross-composite film decreases. At the same time, the compositeness of the hydrophobic carboxymethyl cellulose and the composite film matrix decreases, which affects the barrier properties of the high-strength cross-composite film, and the water vapor permeability increases. In Example 2, polyethylene is not modified by isocyanate, the strength of the composite film decreases, and the barrier properties and hydrophobicity of the high-strength cross-composite film also decrease. In Example 3, dodecyl mercaptan is not added, and the hydrophobicity of the high-strength cross-composite film decreases. Examples 1-3 of the present invention are modified with dodecyl mercaptan to enhance its hydrophobicity, and then amino silicone oil is added for further hydrophobic modification. Polyethylene is modified with isocyanate, and the combination of isocyanate and polyethylene usually strengthens the cross-linking effect between polyethylene molecular chains, thereby improving the mechanical strength and toughness of polyethylene and increasing the strength of the composite film.
[0026] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing a high-strength cross-laminated film, characterized in that: The following steps are involved: Step 1: uniformly mix linear low-density polyethylene, maleic anhydride grafted polyethylene and mesoporous silica, extrude, pelletize and dry to obtain a masterbatch; Step 2: taking high-density polyethylene, linear low-density polyethylene, isocyanate-modified polyethylene, maleic anhydride-grafted polyethylene, masterbatch, paraffin, antioxidant, stabilizer, extruding, blow molding, stretching at 100° C., rotary cutting to obtain a film, cross-compounding to obtain a composite film, drying, and rolling to obtain a cross-compounded film; Step 3: Take polyurethane and acetone, stir evenly, add hydrophobic carboxymethyl cellulose, and disperse by ultrasonic to obtain polyurethane coating; Step 4: Take the cross-composite film, apply the polyurethane coating on the surface of the cross-composite film, and dry it to obtain a high-strength cross-composite film.
2. The method for preparing a high-strength cross-laminated film according to claim 1, characterized in that: The preparation method of the hydrophobic carboxymethyl cellulose comprises the following steps: taking paraffin-coated carboxymethyl cellulose and acetone, stirring evenly, adding dodecyl mercaptan and benzoin dimethyl ether, irradiating with ultraviolet light for 2-2.5 hours in an ice-water bath, centrifuging, adding cyclohexane, stirring evenly, centrifuging, washing, adding isopropanol, adding β-mercaptoethylamine and benzoin dimethyl ether, stirring evenly, irradiating with ultraviolet light for 2-2.5 hours, centrifuging, adding amino silicone oil and ethyl acetate, stirring for 4-5 hours, centrifuging, and drying to obtain the hydrophobic carboxymethyl cellulose.
3. The method for preparing a high-strength cross-laminated film according to claim 1, characterized in that: The cross-composite film comprises the following components, by weight: 85-90 parts of high-density polyethylene, 40-45 parts of linear low-density polyethylene, 20-22 parts of isocyanate-modified polyethylene, 15-16 parts of maleic anhydride-grafted polyethylene, 3-3.5 parts of masterbatch, 6-8 parts of paraffin, 0.8-1 parts of antioxidant, and 0.5-0.6 parts of stabilizer.
4. The method for preparing a high-strength cross-laminated film according to claim 1, characterized in that: The preparation method of the isocyanate-modified polyethylene is as follows: high-density polyethylene, styrene, diisopropyl peroxide, and 3-isopropyl-dimethylbenzyl isocyanate are mixed evenly, heated to 185-190° C., reacted for 10-12 minutes, filtered, and dried to obtain the isocyanate-modified polyethylene.
5. The method for preparing a high-strength cross-laminated film according to claim 1, characterized in that: The preparation method of the mesoporous silica comprises: taking deionized water and ethanol, stirring evenly, adding hexadecyltrimethylammonium bromide, dropping ammonia water to adjust the pH value to 12, ultrasonically dispersing for 20-30 minutes, adding tetraethyl silicate, stirring for 12-14 hours, centrifuging, washing, drying, and calcining to obtain the mesoporous silica.
6. The method for preparing a high-strength cross-laminated film according to claim 2, characterized in that: The preparation method of the paraffin-coated carboxymethyl cellulose comprises the following steps: Step 1: Take carboxymethyl cellulose and hydrochloric acid solution, stir for 10-20 minutes, filter, wash, dry, add a mixed solution of KH570, ethanol and deionized water, ultrasonically disperse, add glacial acetic acid to adjust the pH to 4-4.5, react at 80-85°C for 5-6 hours, wash and dry to obtain modified carboxymethyl cellulose; Step 2: Take hexadecyltrimethylammonium bromide, modified carboxymethyl cellulose and deionized water, ultrasonically disperse for 30-40 minutes, add paraffin, heat to 75-80°C, emulsify for 50-70 minutes, cool, centrifuge and wash to obtain carboxymethyl cellulose coated with paraffin.
7. The method for preparing a high-strength cross-laminated film according to claim 3, characterized in that: The stabilizer is any one or more of tri(2-ethylhexyl)tin sulfosuccinate and tin stearate.
8. The method for preparing a high-strength cross-laminated film according to claim 3, characterized in that: The antioxidant is any one or more of butyl hydroxybenzoate and triphenyl phosphite.
9. A high-strength cross-composite film prepared according to the method for preparing a high-strength cross-composite film according to any one of claims 1 to 8.